Effect of slip to roll ratio on cyclic plastic deformation response at subsurface during rolling contact fatigue - Paul, Surajit Kumar (2023)
The objective of this investigation is to evaluate the cyclic plastic deformation response at the subsurface during rolling contact fatigue (RCF) under the conditions of pure rolling and rolling-sliding. The finite element simulation results indicate that the slip-to-roll ratio (SRR)has an immense effect on the cyclic plastic deformation evolution at the subsurface during RCF. At SRR of 0% (pure rolling), symmetric shear stress cycling is evident at the subsurface, and as a result plastic shakedown takes place. On the other hand, at SRR of 5% (rolling-sliding), asymmetric shear stress cycling is noticed at the subsurface, and consequently ratcheting i.e. progressive accumulation of shear strain is evident. Rolling-sliding results in the shear flow of the subsurface material along the sliding direction.